Scalable and Robust Snapshot Isolation for High-Performance Storage Engines - Alhomssi, Ahmad Adnan; Leis, Viktor (Proceedings of the VLDB Endowment, 2023)
MVCC-based snapshot isolation promises that read queries can proceed without interfering with concurrent writes. However, as we show experimentally, in existing implementations a single long-running query can easily cause transactional throughput to collapse. Moreover, existing out-of-memory commit protocols fail to meet the scalability needs of modern multi-core systems. In this paper, we present three complementary techniques for robust and scalable snapshot isolation in out-of-memory systems. First, we propose a commit protocol that minimizes cross-thread communication for better scalability, avoids touching the write set on commit, and enables efficient fine-granular garbage collection. Second, we introduce the Graveyard Index, an auxiliary data structure that moves logically-deleted tuples out of the way of operational transactions. Third, we present an adaptive version storage scheme that enables fast garbage collection and improves scan performance of frequently-modified tuples. All techniques are engineered to scale well on multi-core processors, and together enable robust performance for complex hybrid workloads.
CRIS-Team Scopus Importer:2023-04-28

The Evolution of LeanStore - Alhomssi, Ahmad Adnan; Haubenschild, Michael; Leis, Viktor (Lecture Notes in Informatics (LNI), Proceedings - Series of the Gesellschaft fur Informatik (GI), 2023)
LeanStore is a high-performance key-value storage engine optimized for many-core processors and NVMe SSDs. This paper provides the first full system overview of all LeanStore components, several of which have not yet been described. We also discuss crucial implementation details, and the evolution of the entire system towards a design that is both simple and efficient.
CRIS-Team Scopus Importer:2023-03-24
Keywords: B-tree; caching; LeanStore; multi-core; SSD; storage engine